Influence of nanoclay on mechanical properties of vinyl ester/acrylated epoxidized palm oil blends - Fakhari, Alireza (2015)
A series of green clay/polymer nanocomposites have been produced using blends of vinyl ester resin (VE) and acrylated epoxidized palm oil (AEPO) via free radical polymerization. A solvent-based processing technique was used to incorporate the bio-resin and nanoclay into vinyl ester resin. The effects of various loadings of bio-resin (5, 10, 15 and 20 wt.%) with 5 wt.% nanoclay on tensile and impact properties of resulting polymer systems were investigated. The results showed that, these bio-based nanocomposites exhibit mechanical properties comparable to those of petroleum-based nanocomposites.